2001
DOI: 10.1007/s002320010035
|View full text |Cite
|
Sign up to set email alerts
|

Are B-type Ca 2+ Channels of Cardiac Myocytes Akin to the Passive Ion Channel in the Plasma Membrane Ca 2+ Pump?

Abstract: The present study demonstrates that B-type Ca2+ channels observed in rat ventricular myocytes markedly reacted to agents known to affect the ion-motive plasma membrane Ca2+-ATPase (PMCA) pump. Chlorpromazine (CPZ)-activated B-type Ca2+ channels were completely blocked by internal application of PMCA pump inhibitors, namely La3+ (100 microm), eosin (10 microm) and AIF(3) (100 microm). Calmodulin (50 U/ml), the main endogenous positive regulator of PMCA, was unable to activate but significantly reduced CPZ-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…ref. 33), and also in native Ca 2ϩ -ATPases of surface (34) and sarcoplasmic reticular (35) membranes; the small flows in the latter case are consistent with an average channel P o on the order of 10…”
Section: Resultssupporting
confidence: 60%
“…ref. 33), and also in native Ca 2ϩ -ATPases of surface (34) and sarcoplasmic reticular (35) membranes; the small flows in the latter case are consistent with an average channel P o on the order of 10…”
Section: Resultssupporting
confidence: 60%
“…As an example, a decreased ATP-dependent Ca 2+ uptake has been shown to occur in PM vesicles isolated from hypertensive rat arterial smooth muscle (Kwan et al , 1980a(Kwan et al , 1980b, and in erythrocytes from animal and human models of hypertension (de la Sierra et al 1990;Vincenzi et al 1986;Postnov and Orlov 1983), and yet cultured hypertensive vascular smooth muscle cells show an increase in the levels of mRNA for PMCA (Monteith et al 1997). This matter is further confused by the observation that PMCA pump protein solubilized from erythrocytes and incorporated into liposomes has been shown to act under conditions like B-type Ca 2+ channels (Pinet et al 2002) that had been earlier reported in cardiac myocytes (Antoine et al 2001). …”
Section: Studies Using Transgenic Micementioning
confidence: 94%
“…The expanded-time scale trace designated "a" in Figure 5D shows the complex gating pattern of B-type channels, which was very similar to that previously observed with cardiac myocytes when B-type channel activity was in- duced by chlorpromazine. 31 Eosin (10 mol/L) completely blocked the channel activity ( Figure 5C), an effect characteristic of B-type Ca 2ϩ channels. 31 When channel recordings were made with mibefradil (20 mol/L) in the pipette, channel activities in freshly isolated and cultured CHF 147 VSMCs were markedly reduced (to 0.24 Ϯ 0.02 and 0.19 Ϯ 0.02, respectively; Figure 5E).…”
Section: Analysis Of B-type Channels In Vsmcs From Control and Chf 14mentioning
confidence: 99%
“…31 Eosin (10 mol/L) completely blocked the channel activity ( Figure 5C), an effect characteristic of B-type Ca 2ϩ channels. 31 When channel recordings were made with mibefradil (20 mol/L) in the pipette, channel activities in freshly isolated and cultured CHF 147 VSMCs were markedly reduced (to 0.24 Ϯ 0.02 and 0.19 Ϯ 0.02, respectively; Figure 5E). …”
Section: Analysis Of B-type Channels In Vsmcs From Control and Chf 14mentioning
confidence: 99%